Climate-growth relationships and growth trends of Cedrus libani, Pinus brutia, and Pinus nigra subsp. pallasiana in the Boz Mountains (Western Türkiye) - Eren Özer; Raziye Oğlakcı; Tuğba Erkan; Aylin Güney (Turkish Journal of Forestry, 2025)
The ongoing climate change is increasingly affecting the growth conditions of forest trees. In the Mediterranean region, a reduction in precipitation and an increase in temperature are anticipated, which will have an adverse impact on tree growth. We used dendrochronology methods to analyze the impact of climate variables (air temperature, precipitation, relative humidity, and vapor pressure deficit) on stem growth of planted Taurus cedar (Cedrus libani A. Rich) and natural occurring Turkish pine (Pinus brutia Ten.) and Anatolian black pine (Pinus nigra subsp. pallasiana (Lamb.) Holmboe) growing in the Boz Mountains, Western Türkiye. We further investigated their growth trends based on basal area increment to detect growth differences between these three ecologically and economically important forest tree species. Taurus cedar showed a positive growth trend indicating good tree vitality. Turkish pine and black pine showed neither a positive nor a negative growth trend over the past 25 years. Turkish pine exhibited the greatest year-to-year variability in tree ring width and basal area increment and was the most sensitive to climate, resulting in significant response function and correlation analysis results. Turkish pine growth was most limited by winter precipitation and current year’s July precipitation. Radial growth in black pine was negatively correlated to high temperatures and dry conditions in current year May. Our results further showed, that Taurus cedar was the least sensitive to year-to-year climate variability.